A cross sectional study to assess the severity of meibomian gland dysfunction and its association with dyslipidemia - Nithisha, T. M.; Thomas, Linto Mathew; Joshi, Isha S.; P., Tejaswini (International Journal of Advances in Medicine, 2023)
Background: Studies have linked increased cholesterol esters in meibomian secretions to patients with meibomian gland dysfunction. Dyslipidemia has been linked to the development of MGD. This study of serum lipid profile in established cases of MGD. Methods: A cross sectional study was conducted in department of ophthalmology at Rajarajeswari medical college and hospital Kambipura, Bengaluru from January 2021 to June 2022. 75 study participants with clinical diagnosis of MGD were included. Results: The mean age of the study participants was found to be 55.97±14.019. Mild MGD grade was found in 32% and 26.7% of the study participants in the right eye and left eye respectively. Moderate MGD grade was 38.7% and 42.7% of the study participants in the right and left eye respectively. 4% each of the study participants had very severe MGD grade in the right and left eye respectively. Marx line grading of 1 was found in 40% and 46.7% of the study participants in the right eye and left eye respectively. Marx line grading of 2 was found in 54.7% and 36% of the study participants in the right and left eye respectively. Marx line grading of 3 was 5.3% and 17.3% of the study participants in right left eye respectively. severity of MGD grading of the study participants increases, the Lipid profile values also increases. The association was statistically significant between the MGD grading and lipid profile. Conclusions: MGD patients exhibit a higher degree of total cholesterol, LDL, lower degree of HDL in their serum lipid profiles than normal reference levels and the severity of MGD increases, the values of lipid profile increase. Elevated serum cholesterol was associated with MGD.